Slay [large type] - Morris, Brittney (Thorndike Press large print striving reader collection., 2020)
An honors student at Jefferson Academy, seventeen-year-old Kiera enjoys developing and playing Slay, a secret, multiplayer online role-playing game celebrating black culture, until the two worlds collide.